2020
DOI: 10.3390/s20102821
|View full text |Cite
|
Sign up to set email alerts
|

Smart Sensing Using Electromagnetic Waves for Inspection of Defects in Rock Bolts

Abstract: The stability of tunnels and rock slopes is adversely affected by defects in rock bolts. This study investigates the suitability of the smart sensing method using electromagnetic waves for inspecting defects in rock bolts. Experiments were performed with one fully grouted and eight defective rock bolts, out of which five have non-grouted parts at the ends with different non-grouted ratios, and three have different types of voids. Electromagnetic waves were generated and detected using a time domain reflectomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Overall, these values were similar, regardless of the probe length. Since the lengths of HETDR probes were higher than that of the conventional TDR probe, attenuation and dispersion may be more obvious in the case of the HETDR probe, causing a significant increase in the rising time [28]. Consequently, the travel time, dielectric constant, and SWC obtained through the HETDR probe were higher than those obtained through the conventional TDR probe.…”
Section: Hetdr Versus Conventional Tdrmentioning
confidence: 96%
See 1 more Smart Citation
“…Overall, these values were similar, regardless of the probe length. Since the lengths of HETDR probes were higher than that of the conventional TDR probe, attenuation and dispersion may be more obvious in the case of the HETDR probe, causing a significant increase in the rising time [28]. Consequently, the travel time, dielectric constant, and SWC obtained through the HETDR probe were higher than those obtained through the conventional TDR probe.…”
Section: Hetdr Versus Conventional Tdrmentioning
confidence: 96%
“…Lee et al [27] reported that the TDR is an effective method for detecting necking defects in bored piles. Another application of the TDR method is the identification of defects in rock bolts used to improve the stability of tunnels and rock slopes [28]. Furthermore, Yu et al [29] suggested the use of a circular TDR system to enhance the resolution of scour depth monitoring around piers and bridge abutments.…”
Section: Introductionmentioning
confidence: 99%
“…A non-destructive test method for monitoring rock bolt condition [186] is required and ultrasonic methods have previously been applied. While these sensors provide satisfactory performance, the ultrasonic energy from the bolt continues to pass into the nearby rock [187] and the ultrasonic sensors are costly, and specific skills are required for the data analysis [188]. Therefore, using piezoceramic transducers with electro-mechanical impendence sensors to monitor rock bolts is a new alternative [189].…”
Section: Rock Bolt Tension/stress Assessmentmentioning
confidence: 99%
“…A general procedure for the installation of rock bolts includes drilling, the insertion of rock bolts, and grouting. Drill hole wall collapse, groundwater flow, poor grout mixture, and leakage of grout into the surrounding voids are some of the factors responsible for affecting the quality of grouting used in rock bolting operations [2]. There are various types of rock bolts that are available to us.…”
Section: Introductionmentioning
confidence: 99%